Front-end design for visible light communications systems - Camacho, Pedro Alexandre Armas (2018)
Communications are vital in the world today. Everything is connected and this means that communication technologies are constantly being pushed to their limits. Any kind of development and improvement that can be done to increase networks capabilities, will ﬁnd use in some speciﬁc application, or even in more common technologies if such is justiﬁed. One such case is VLC, it can be used to improve other communication methods capabilities, or as standalone solution, providing advantage in certain scenarios where regular wirelesscommunicationsmethodswouldnotperformaswell,orwouldnotsuit theapplication. VLCalsooffersthegreatadvantageofutilisinganewmedium of transmission for telecomunication systems, which is the visible light spectrum, and is not yet overused and overregulated as other typical mediums. This work was done in partnership with the integrated circuit systems groupd ofInstitutodeTelecomunicaçõesAveiroandaimstostudyanddevelopoptical front end systems for VLC to be used in future projects by this group.